Clinical and cost–effectiveness of insulin degludec: from clinical trials to clinical practice. (May 2015) - Evans, Marc; McEwan, Phil
The increasing prevalence of diabetes presents one of the greatest challenges to healthcare provision in modern times, with the cost of treating diabetes and its related complications representing a significant proportion of healthcare expenditure. In recent years, many new therapeutic entities have been developed with the aim of improving glycemic control, and thus slowing the development of micro- and macrovascular complications. Insulin degludec is a new-generation basal insulin analog with an ultra-long duration of action and low day-to-day and hour-to-hour intrapatient variability in blood glucose-lowering action. In this review, we consider evidence from clinical trials and real-world studies demonstrating the clinical benefits and cost–effectiveness of insulin degludec and its potential for improving patient care.